Order in multiplicity : homonymy in the philosophy of Aristotle - Shields, Christopher John (Oxford Aristotle studies, 1999)
Aristotle attaches particular significance to the homonymy of many central concepts in philosophy and science: that is, to the diversity of ways of being common to a single general concept.
Keywords: Aristotle : Contributions in methodology; Aristoteles, : 384 eaa.-322 eaa; Methodology : History; antiikin filosofia; homonymia; antikens filosofi; homonymi